Implementasi Pelayanan Travel Haji dan Umroh pada Ja-ma’ah di PT. HEMA Tour and Travel & PT. Noor Alia Bondowoso - Umi Khoidatul Avifah; Romzatul Widad (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The Hajj and Umrah travel sector in Indonesia is experiencing very significant growth with the increasing interest of the Muslim community in Hajj and Umrah. However, this has very serious challenges, such as the emergence of unauthorized travel and declining service quality which has a direct impact on pilgrims' satisfaction and pilgrims' spiritual experience. This study aims to provide a comprehensive picture of the quality of customer service provided by PT Hema Tour and Travel & PT Noor Alia Bondowoso, as well as to provide practical recommendations for other industry players who want to improve their services and to create better service standards, which in turn will improve the experience of Hajj and Umrah for consumers in the future. This research uses qualitative descriptive analysis with a comparative approach. This research was conducted at PT HEMA Tour and Travel & PT Noor Alia Bondowoso. Data collection techniques were carried out using interviews, observation and documentation. The results of research on the implementation of Hajj and Umrah travel in consumer services at PT. Hema Tour and Travel & PT. Noor Alia Bondowoso show that the two companies have good service in various aspects both from the aspects of administration, price, transportation, accommodation, consumption, guidance and protection. This shows the commitment of both companies in providing the best experience for pilgrims. However, PT Noor Alia Bondowoso is superior in several aspects, such as a savings system that can facilitate pilgrims in planning Umrah without being burdened, a variety of package options, a variety of accommodation options and more intensive ritual guidance. With all the best services provided by the two companies, it has succeeded in increasing the positive image of the two companies in the community, especially in the Bondowoso area.